Unia Europejska w wielobiegunowej perspektywie rozwoju gospodarki światowej - Puślecki, Zdzisław W. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article concerns the new tendencies in the economic development of the European Union at the beginning of the 21st century. It shows the new conditions which are connected with the increase of the Russian activity in energy sphere. For the European Union it is very important because of its dependence on Russian oil and gas. In this situation, the EU must diversify the energy sources. In the new circumstances of the development of the global economy and the global trade, the eyes of the world, and the EU too, have been turned to China. This country seems to be a production superpower, able to change the world trade. In many areas it possesses comparative advantages. The access of China to WTO was a historical decision, the evidence of evolution which was taking place within that organisation, giving it a more universal, global form. This means also that it expands on a huge market which can open itself up for foreign competition and for the EU. A long-termed stability of that country depends on the fast economic growth, which is possible only when the foreigners become convinced that China is a partner able to play global roles. Both the world and China should be properly prepared for this. China will overtake the United States in mid-century. Thus American dominance should endure until mid-century. Afterwards, Asian demands for modification to the international system will likely increase, and unless resolved, will be increasingly likely to be imposed by force. The question raised by this empirically grounded extrapolation is whether the West and the EU, will see China's rise as an opportunity for co-operation or for conflict. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 502-513